2011
DOI: 10.2478/10004-1254-62-2011-2102
|View full text |Cite
|
Sign up to set email alerts
|

Work Ability Assessment in a Patient with Wilson's Disease

Abstract: Work Ability Assessment in a Patient with Wilson's DiseaseWilson's disease (WD) is a rare, progressive autosomal recessive disorder characterised by impaired transport and excessive accumulation of copper in the liver, brain, and other tissues. The disease is diagnosed based on clinical manifestations and screening tests results. Work ability assessment of patients with WD is based on the analysis of liver, kidney, neurological, and cognitive impairments, and takes into account patient's level of education.Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Wilson's disease is a rare, progressive, autosomal recessive disorder characterised by impaired transport and excessive accumulation of copper in the liver, brain, and other tissues [152]. The condition is due to mutations in the Wilson disease protein of ATP7B gene (located on chromosome 13q14.3) [68], by impaired copper incorporation to ceruloplasmin and biliary copper excretion.…”
Section: Wilson's Disease or Hepatolenticular Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilson's disease is a rare, progressive, autosomal recessive disorder characterised by impaired transport and excessive accumulation of copper in the liver, brain, and other tissues [152]. The condition is due to mutations in the Wilson disease protein of ATP7B gene (located on chromosome 13q14.3) [68], by impaired copper incorporation to ceruloplasmin and biliary copper excretion.…”
Section: Wilson's Disease or Hepatolenticular Degenerationmentioning
confidence: 99%
“…The condition is due to mutations in the Wilson disease protein of ATP7B gene (located on chromosome 13q14.3) [68], by impaired copper incorporation to ceruloplasmin and biliary copper excretion. It is characterisied by a hepatic cirrhosis, neurological manifestations (dystonia, dysarthria, muscle weakness, vertigo), psychiatric manifestations, renal disease, and copper deposition in the cornea -Kayser-Fleischer ring ( Figure 5) [53,54,152]. The treatment of Wilson's disease involves avoidance of foods rich in copper and any supplements containing copper and drug treatment with chelating agents that remove the excess copper from the body (D-penicillamine, Zn acetate) [153].…”
Section: Wilson's Disease or Hepatolenticular Degenerationmentioning
confidence: 99%
“…Schmitt et al (2011), in a 40 years follow-up study with 36 patients diagnosed with WD reported that 25% of the patients had neuropsychiatric manifestations where the common symptoms were attention deficit, changes in personality, irritability and hypersomnia. Other studies attribute the changes in mood and personality to a dopamine deficit present in the disease (Litwin, Gromadzka, Członkowska, Poniatowska, & Poniatowska, 2013;Günther, Villmann & Hermann, 2011;Schmitt et al, 2011;Popević, Kisić, Đukić, & Bulat, 2011;Hegde, Sinha, Taly, & Vasudev, 2010).…”
Section: Introductionmentioning
confidence: 99%